The Multi-Level Mechanism of Action of a Pan-Ras Inhibitor Explains its Antiproliferative Activity on Cetuximab-Resistant Cancer Cells - Tisi, Renata; Spinelli, Michela; Palmioli, Alessandro; Airoldi, Cristina; Cazzaniga, Paolo; Besozzi, Daniela; Nobile, Marco S.; Mazzoleni, Elisa; Arnhold, Simone; De Gioia, Luca; Grandori, Rita; Peri, Francesco; et al. (Frontiers in Molecular Biosciences, 2021)
Ras oncoproteins play a crucial role in the onset, maintenance, and progression of the most common and deadly human cancers. Despite extensive research efforts, only few mutant-specific Ras inhibitors have been reported. We show that cmp4 – previously identified as a water-soluble Ras inhibitor– targets multiple steps in the activation and downstream signaling of different Ras mutants and isoforms. Binding of this pan-Ras inhibitor to an extended Switch II pocket on HRas and KRas proteins induces a conformational change that down-regulates intrinsic and GEF-mediated nucleotide dissociation and exchange and effector binding. A mathematical model of the Ras activation cycle predicts that the inhibitor severely reduces the proliferation of different Ras-driven cancer cells, effectively cooperating with Cetuximab to reduce proliferation even of Cetuximab-resistant cancer cell lines. Experimental data confirm the model prediction, indicating that the pan-Ras inhibitor is an appropriate candidate for medicinal chemistry efforts tailored at improving its currently unsatisfactory affinity.